1997
DOI: 10.1074/jbc.272.6.3733
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Expression and Redundant Activation of Mesenchymal Fibroblast Growth Factor (FGF) Receptors by Alternatively Spliced FGF-8 Ligands

Abstract: FGF-8 is a member of the family of fibroblast growth factors and is expressed during vertebrate embryo development. Eight potential FGF-8 isoforms are generated by alternative splicing in mice, several of which are expressed during embryogenesis in epithelial locations. The significance of the multiple isoforms is currently unknown. In this report, we investigate the expression patterns and the specificity of the FGF-8 isoforms for known fibroblast growth factor (FGF) receptors. RNAs for seven of the eight pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 35 publications
2
59
1
Order By: Relevance
“…Studies have demonstrated that it acts through FGFR2c, FGFR3c, FGFR4 and FGFR1 (MacArthur et al, 1995c;Ornitz et al, 1996;Blunt et al, 1997;Kouhara et al, 1994) and we have shown, by PCR and immunohistochemistry, that FGFR4 and FGFR1 are present in breast cancers allowing a potential autocrine loop to develop. If there are a proportion of breast cancers that are driven by such a loop then interrupting this cycle could lead to the development of novel therapies.…”
Section: Discussionsupporting
confidence: 54%
“…Studies have demonstrated that it acts through FGFR2c, FGFR3c, FGFR4 and FGFR1 (MacArthur et al, 1995c;Ornitz et al, 1996;Blunt et al, 1997;Kouhara et al, 1994) and we have shown, by PCR and immunohistochemistry, that FGFR4 and FGFR1 are present in breast cancers allowing a potential autocrine loop to develop. If there are a proportion of breast cancers that are driven by such a loop then interrupting this cycle could lead to the development of novel therapies.…”
Section: Discussionsupporting
confidence: 54%
“…Four receptors have been detailed (designated FGFR 1 -4) and multiple splice variants of these receptors have been described (Ornitz et al, 1996). FGF8 is known to activate FGFR2, 3 and 4, as well as FGFR1 if applied in high concentrations (Ornitz et al, 1996;Blunt et al, 1997). In addition, developmental studies have shown that it is the c splice forms of FGFRs that are the preferred targets of FGF8 and these are expressed predominantly in the mesenchymal tissue (MacArthur et al, 1995b).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, FGF8 may well adopt both a paracrine and an autocrine role. The FGF8 isoforms themselves are known to have relatively specific binding characteristics (Blunt et al, 1997). Human FGF8a, for example, does not activate any of the FGFRs, while the FGF8b and e isoforms are known to interact with FGFR3IIIc and FGFR4 (Blunt et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Investigation on the involvement of FGF8b in hormone-related cancers was indeed based on the initial discovery of FGF8 (androgen-induced growth factor) in an androgen-dependent mouse mammary carcinoma cell line (Tanaka et al, 1992) and detection of FGF8 overexpression in human breast and prostate cancers (Tanaka et al, 1995;Leung et al, 1996;Gnanapragasam et al, 2002). Further genomic and functional characterization of the FGF8 family demonstrated that the FGF8b isoform (one of the four human FGF8 isoforms: FGF8a, b, e and f (Gemel et al, 1996)) possesses the greatest mitogenic and, more importantly, the greatest transforming activity than the other isoforms, both in vitro and in vivo (MacArthur et al, 1995a(MacArthur et al, , 1995bBlunt et al, 1997;Song et al, 2000;Olsen et al, 2006). It is believed that FGF8b is one of the most important FGF8 isoforms in human carcinogenesis Gnanapragasam et al, 2003), although the exact physiological function of each isoform is yet-to-be fully revealed.…”
Section: Introductionmentioning
confidence: 99%